IMPLEMENTING LANDSCAPE ECOLOGY PRINCIPLES FOR SUSTAINABLE NATURAL RESOURCE MANAGEMENT IN INDONESIAN FOREST AREAS CONTEXTS - Putri Arvina (Pusat Unggulan Ipteks-PUI Universitas Jambi, 2025)
Landscape ecology principles play an important role in sustainable natural resource management, especially in the context of forest area management. This approach focuses on understanding the spatial relationships between ecosystem elements and the importance of ecological connectivity to maintain ecological functions and biodiversity. Literature studies have shown that the application of landscape ecology can help design more effective forest management, taking into account factors such as habitat fragmentation, climate change, and pressures from human activities. Several studies have identified the importance of landscape mapping and ecosystem modeling to manage conservation areas with a science-based approach. The implementation of these principles also includes ecosystem restoration, water management, and reduction of damage from deforestation, which can increase environmental carrying capacity. However, major challenges remain, especially related to policies, community participation, and awareness of the importance of landscape ecology-based management.